The deterrence effect of capital punishment in Malaysia / Mohd Hisham Ahmad Nazri, Mark Anthony Martin, Wan Abdul Rahim Wan Mahamood - Ahmad Nazri, Mohd Hisham; Martin, Mark Anthony; Wan Mahamood, Wan Abdul Rahim (2011)
The purpose of death penalty has always been for deterring the community from repeating crimes. Crimes that are punishable by death are considered the ultimate deterrent to the society. In Malaysia, crimes that are punishable by death are crimes of murder, drug related offences, threat against the country or the Yang Di-Pertuan Agong, kidnapping, possession and smuggling of illegal firearms and also waging war against the state and the country. In the case of R v Melnyk, Justice Gerein, define deterrence as a principle or objective of sentencing a person guilty of a crime which ensures that the punishment is sufficient to deter the guilty person, and others, from committing the same crime1. Moreover, In R v Morrissette, Justice Culliton wrote, in the context of a discussion on the factors to take into account when sentencing, he said, "Deterrence is also an important factor. The problem is different if the purpose of sentence is to deter the offender from repeating the offence from that if the purpose is to deter others who may be inclined to commit the same offence. In neither case does it necessarily follow that a long sentence is required to achieve the purpose.